THE INVERSE APPROACH TO THE QUESTION OF IMPROVING THE WEAR RESISTANCE OF THE ENGINE CYLINDER DBC GROUP - N. K. Sanaev; V. P. Tynyanskii (Вестник Дагестанского государственного технического университета: Технические науки)
The scientific approach to the question of durability of kinematics - the dynamic pair of cylinder liner - piston rings, which depend primarily on the roughness is considered. In this paper as the optimal roughness values adopted the inverse roughness obtained after the break-in cylinder liners processed by rolling.The graphs of the weight and linear wears of indicated pairs are shown. A solution for the issue determined by the new technology producer's risk are offered.